ҚАРАҚАЛПАҚ НАҚЫЛ-МАҚАЛЛАРЫНДА ЖЫЛҚЫ АТАМАЛАРЫНЫҢ КВАНТИТАТИВ-ТИПОЛОГИЯЛЫҚ ӨЗГЕШЕЛИГИ - Искендерова, Е. (ILIM hám JÁMIYET, 2018)
The article is devoted to the study of quantitative-typological peculiarities of cattle-breeding vocabulary in proverbs and sayings of the Karakalpak language, the words denoting the names of horses, in particular.